2008
DOI: 10.1007/s11102-008-0134-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cabergoline therapy is not associated with valvular heart disease in patients with prolactinomas

Abstract: Ergot-derived dopamine receptor agonists, especially pergolide and cabergoline, have been associated with an increased risk of valvular heart disease in patients treated for Parkinson's disease. Cabergoline at lower doses than those employed in Parkinson's disease is widely used in patients with prolactinomas, because of its high efficacy and tolerability; however, its safety with regard to cardiac valve disease is unknown. In order to assess the prevalence of cardiac valve regurgitation in patients with prola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
66
3
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 17 publications
9
66
3
4
Order By: Relevance
“…Over the past 5 years, 15 independent studies (13,14,15,16,17,18,19,20,21,22,23,24,25,26,27) (Table 1) have investigated the effects of CAB on the development of CRVD in patients with prolactinomas. Overall, these studies have reported a median CRVD rate of w4%, with the prevalence of CRVD ranging from 54% (13), 40% (24), 15% (17) to 0% (15,16,19,21) and valvulopathy being assessed according to the International Guidelines suggested by the American Society of Echocardiography (28,29) in all studies and also according to the European Association of Echocardiography (30,31) in ten studies (13,16,17,18,20,22,23,25,26,27). Moreover, a significant correlation between cumulative dose of CAB and prevalence of valve disease has been demonstrated in only two reports (13,24), whereas the vast majority of studies have agreed on safety of treatment with CAB on valvulopathy in hyperprolactinemic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 5 years, 15 independent studies (13,14,15,16,17,18,19,20,21,22,23,24,25,26,27) (Table 1) have investigated the effects of CAB on the development of CRVD in patients with prolactinomas. Overall, these studies have reported a median CRVD rate of w4%, with the prevalence of CRVD ranging from 54% (13), 40% (24), 15% (17) to 0% (15,16,19,21) and valvulopathy being assessed according to the International Guidelines suggested by the American Society of Echocardiography (28,29) in all studies and also according to the European Association of Echocardiography (30,31) in ten studies (13,16,17,18,20,22,23,25,26,27). Moreover, a significant correlation between cumulative dose of CAB and prevalence of valve disease has been demonstrated in only two reports (13,24), whereas the vast majority of studies have agreed on safety of treatment with CAB on valvulopathy in hyperprolactinemic patients.…”
Section: Introductionmentioning
confidence: 99%
“…After the publication of the papers, which showed an increased risk of valve regurgitation after treatment with pergolide and cabergoline in patients with Parkinson's disease, six cross-sectional studies have evaluated the association between valve regurgitation and the use of cabergoline in patients treated for prolactinoma, including the study by Wakil et al published in this edition of the European Journal of Endocrinology (Table 1) (10)(11)(12)(13)(14)(15). These studies included a total of 413 patients, treated with cabergoline for 45-79 months.…”
Section: Introductionmentioning
confidence: 99%
“…Cabergoline, which possesses a complete 5HT 2b agonistic activity, is the drug of choice in the treatment of prolactinomas, but the results of observational studies investigating the risk of FVHD in these patients are still controversial. Some of them have reported no relevant findings (8,9,10,11,12), five trials have observed clinically insignificant valvular changes (13,14,15,16,17), and only one study has reported an increased prevalence of moderate tricuspid regurgitation with a cumulative dose-dependent risk (18). Published data on the potential profibrotic effect of bromocriptine, a partial 5HT 2b agonist, are exclusively limited (19).…”
Section: Introductionmentioning
confidence: 99%